2010
DOI: 10.2225/vol13-issue5-fulltext-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antiyeast compound and probiotic properties of a starter Lactobacillus plantarum DW3 for possible use in fermented plant beverages

Abstract: Lactobacillus plantarum DW3 produced antifungal compounds that inhibited the growth of Rhodotorula mucilaginosa DKA, contaminating yeast in fermented plant beverages (FPBs) and various potential human pathogens. Phenyllactic acid (PLA) identified by gas chromatography-mass spectrometry (GC-MS) was produced at 31 mg/L PLA in MRS medium and 5 mg/ml inhibited growth of the target yeast in vitro by 90%. Other inhibitors were also present but not specifically identified. Results of in vitro tests showed that DW3 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Recently, an in vivo mouse acute oral toxicity safety assay deemed Lact. plantarum DW3, an antifungal starter used in plant fermented beverages, most likely to be safe for human consumption (Kantachote et al 2010). Previous experiments have determined that the compound(s) in question are nonproteolytic and inactivated after neutralization (S. Crowley, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in vivo mouse acute oral toxicity safety assay deemed Lact. plantarum DW3, an antifungal starter used in plant fermented beverages, most likely to be safe for human consumption (Kantachote et al 2010). Previous experiments have determined that the compound(s) in question are nonproteolytic and inactivated after neutralization (S. Crowley, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Blood sample was also used to check fungaemia. The growth rate (GR), spleen weight index and liver weight ratio were calculated according to Kantachote et al [43]. …”
Section: Methodsmentioning
confidence: 99%
“…Lb. plantarum produces antimicrobial compounds including organic acids such as phenyllactic acid that exerts inhibitory activity against contaminating yeasts [19]. Also Durlu-Özkaya et al [20] showed that Lb.…”
Section: Growth Performance Of the Co-culturesmentioning
confidence: 99%